Monitoring pharmaceuticals and personal care products to assess water quality changes and pollution sources in a drinking water reservoir catchment - Kinga Ślósarczyk; Filip Wolny; Andrzej J. Witkowski (Water Resources and Industry)
This research aimed to identify sources of pharmaceuticals and personal care products (PPCPs) in the Kozłowa Góra catchment, southern Poland, and assess their temporal and spatial variability. PPCP monitoring was conducted from 2020 to 2022. Samples were taken from the Brynica River and other streams. Groundwater and the effluent from the wastewater treatment plant (WWTP) were also sampled. The monitoring screened 109 PPCPs using the LC-MS/MS method. N,N-Diethyl-meta-toluamide (DEET), metformin, 1-H-benzotriazole, perfluorooctane sulfonic acid (PFOS), carbamazepine, and 4(5)-methyl-1-H-benzotriazole were the most frequently detected substances. The highest total PPCP concentrations in surface waters reached 30790 ng/L, with up to 53 compounds detected at one point. Results indicated temporal and spatial variability, with higher concentrations and more PPCPs during winter periods and increased contamination downstream from the WWTP. DEET was the only contaminant consistently found in the shallow aquifer discharged into the Brynica, however groundwater impact on the river's water quality is negligible. The study confirmed the WWTP as the primary source of PPCPs, with the number of detected substances in effluent samples amounting to 65 and their total concentrations reaching 148265 ng/L. Additional sources included the airport, uncontrolled/illegal domestic sewage discharges, and human activities in forested areas. This study was the first in Poland to implement a PPCP monitoring approach in a drinking water reservoir catchment area using multiple monitoring points and sampling campaigns. The results revealed the constant presence of PPCPs in a moderately urbanised catchment area, highlighting the importance of regular monitoring to understand PPCP migration in the environment.